MOVIE THERAPY AS A TOOL TO DEVELOP PROSOCIAL BEHAVIOR OF CHILDHOODS - Wa Ode Lili Andriani Nasri; Hengki Satrianta (Herodotus: Jurnal Pendidikan IPS, 2018)
Abstract. The phase of human life begins on entering the prenatal period and will end in late adulthood. Childhoods is critical age or golden age.  This article aim to describe how movie therapy can used as a tool to develop prosocial behavior of childhoods. This article is analyzed by using literature review. Through literature review found that movie therapy can used as a tool to develop prosocial behavior of childhoods. Implications of this findings in teacher and especially counselors must to try this method to help childhoods with the lack of prosocial behavior. So, happy watching! Keywords: movie therapy, prosocial behavior